PELANGGARAN TERHADAP MEREK TERKENAL YANG DITIRU OLEH PELAKU USAHA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Wahedani, Ahmad; Sugiarti, Yayuk; Fithry, Abshoril (Fakultas Hukum Universitas Wiraraja, 2023)
The large level of consumption that makes other industries take advantage of well-known brands to gain profits and make famous brands by imitating or counterfeiting these brands. The circulation of counterfeit or imitation goods (hereinafter referred to as KW) has been widely circulating in the market, the widespread circulation of counterfeit goods has made many parties uneasy. The act that causes this loss is an act of violation of the mark. One of the main issues that can be put forward is what is the responsibility for business actors who imitate well-known brands and how is the legal protection for owners of well-known brands that are imitated. The objectives to be achieved are to find out and analyze the responsibility for business actors who imitate well-known brands and also to find out and analyze how the legal protection for owners of famous brands that are imitated is. The research method used in this thesis research is Normative Jurisdiction. The research method used aims to complete this thesis research. This type of research is normative, namely the type of research that emphasizes the applicable laws and regulations. Responsibilities for business actors who imitate well-known marks in the form of civil law can be sued for compensation because it is an unlawful act to use trademark rights without obtaining prior approval and permission from the owner/holder of the rights to the registered mark. In criminal sanctions according to the provisions of Article 100-102 Law Number 20 of 2016 concerning Marks and Geographical Indications by trading counterfeit goods using well-known brands.